Analysis of Validation Development of Learning Media of Microscope Digital Portable Auto Design to Improve Student Creativity and Problem-Solving Ability - Adi Hardiyansyah; Aris Doyan; A Wahab Jufri; Susilawati Susilawati; Jamaluddin Jamaluddin (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: This study aims to produce a valid product in the form of learning media of a microscope digital portable auto design, using the Dick and Carey development model. Media portable digital microscope learning auto design was developed to enhance the scientific creativity and problem-solving abilities of students in light material and optical devices. However, at this writing focused on the process of validation testing through validation tests on the development of learning media. The final result of this research is to produce a learning media development product in the form of a valid portable digital design microscope. Based on the results of the validation test by 3 material experts and the validity media, the media were at an average of 97.78% with very good criteria. Keywords: Learning Media; Microscope Digital Portable; Problem-Solving